Migrant Status and Lone Motherhood – Risk Factors of Female Labour Force Participation in Switzerland - Nadja Milewski; Emanuela Struffolino; Laura Bernardi (Lone Parenthood in the Life Course, 2018)
Compared to non-migrant mothers in couples, migrant lone mothers face a much higher risk of being out of the labour market, given that both lone motherhood and international migration have been shown to be strongly related to non-employment. In this chapter, we analyse the labour force participation of immigrant women and non-migrants living in Switzerland, and compare them by distinguishing between mothers in couples and lone mothers. We use data from the Swiss Labour Force Survey (wave 2008; N = 6814). These data allow us to account for intra-group variation among the immigrants by distinguishing them by their migrant generation and their country of origin. The analyses include women aged 20–54 who were living with at least one child under age 18. The dependent variable in the multinomial regression analyses is employment status, differentiating between full-time employment, long and short part-time employment, and non-employment. Results indicate that lone motherhood prevalence is similar among migrant and Swiss mothers (11%). In both groups, lone mothers are less likely to be in employment than mothers in couples. However, we find variation among lone mothers by migrant status: migrants have a higher non-employment rate overall. Among the employed women, migrant lone mothers tend to work full time, whereas non-migrant lone mothers tend to work part time. For lone mothers being an international migrant is therefore associated with an increased risk not only of being out of the labour force, but also of facing difficulties linked to work-family reconciliation. These results are relevant for the design of appropriate policies for migrants, lone parents, and work-family reconciliation, particularly in a societal context like Switzerland, where child care services are insufficient and the number of mothers who work full time is relatively small.
Keywords: 330